An eco-innovative framework development for sustainable consumption and production in the construction industry - Ma, Li; Wang, Liang; Skibniewski, Miroslaw J.; Gajda, Waldemar (Technological and Economic Development of Economy, 2019)
Sustainable consumption and production have been increasingly required in the construction industry. However, previous studies have not yet comprehensively developed evaluation tools and methods to implement sustainable consumption and production. To achieve this objective, we utilized the eco-innovation, which provides effective analysis of sustainable consumption and production for the construction firms by eliminating subjectivity and ambiguity of evaluations. We adopted the fuzzy set theory to overcome the uncertainty occurring from the judgments of experts and utilized decision-making trial and evaluation laboratory approach to analyse the causal relationships between our methods and evaluation criteria. The results showed that environment and sustainable consumption are the key factors, while life cycle assessment, eco-labels, and environmental certification as well as improving eco-efficiency are critical to realizing sustainable consumption and production. The study enhances the understanding of the major players to achieve sustainable consumption and production, and link sustainable consumption and production with the eco-innovative practices. Our approach also improves the assessment accuracy, and the results provide viable suggestions for practical applications.First published online 31 May 2019